Wildfires drive multi-year water quality degradation over the western United States - Carli P. Brucker; Ben Livneh; Fernando L. Rosario-Ortiz; Fangfang Yao; A. Park Williams; William C. Becker; Stephanie K. Kampf; Balaji Rajagopalan (Communications Earth & Environment, 2025)
Abstract Wildfires can dramatically alter water quality, resulting in severe implications for human and freshwater systems. However, regional-scale assessments of these impacts are often limited by data scarcity. Here, we unify observations from 1984–2021 in 245 burned watersheds across the western United States, comparing post-fire signals to baseline levels from 293 unburned basins. Organic carbon and phosphorus exhibit significantly elevated levels (p ≤ 0.05) in the first 1–5 years post-fire, while nitrogen and sediment show significant increases up to 8 years post-fire. During peak post-fire response years, average carbon, nitrogen, and phosphorus concentrations are 3–103 times pre-fire levels, and sediment 19–286 times pre-fire concentrations. Higher responses are linked with greater forested and developed areas, which respectively explain up to 31 and 33% of inter-basin response variability. Overall, this analysis provides strong evidence of multi-year water quality degradation following wildfires in the western United States and highlights the influence of basin and wildfire features. These insights may aid water managers in preparation efforts, increasing resilience of water systems to wildfire impacts.